Robo-advisors as Automated Personal Financial Planners – SWOT Analysis - Waliszewski, Krzysztof; Zięba-Szklarska, Marta (Journal of Finance and Financial Law, 2020)
Automatic financial consulting (robo-advice) is a financial innovation in the area of personal financial planning, and in particular investment consulting classified as fin-tech (financial technology). The main disadvantage of traditional investment advice is limited availability due to the required amount of assets and high management costs. These disadvantages are answered by robo-advice, using artificial intelligence and algorithms without the participation of a physical adviser, thereby reducing or abolishing minimal assets and reducing costs [Kocianski 2016]. The purpose of the article is to analyze strengths and weaknesses as well as opportunities and threats of robo-advisors, especially when compared to traditional financial advisors. This paper is an analysis of a history, regulations, application, functionality and development of Robo-Advice. The concept of Robo-Advice was critically analysed, with presentation of current strength and weaknesses, as well as opportunities and threats. We aimed showing that Robo-Advice should be innovative, feature a new approach, and should transform the current financial consulting. There are still, however, many opportunities and challenges in this field, which await discovering. The article uses the SWOT analysis method, analysis of the literature and reports. As indicated by the analysis, robo-advisors are not a threat to traditional financial advisors, but their complement, which makes the hybrid model connecting a physical advisor assisted by technological solutions (robo-advisors) most likely. This thesis is also confirmed by the small scale of robo-advisors’ activity compared to traditional advisors measured by the market penetration rate (in 2023 about 2% assets under management).